Mediação de pré-processual como instrumento de promoção do acesso à justiça: análise dos dados do CEJUSC da Comarca de Ponta Grossa-PR - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2021)
In 2010, the CNJ issued Resolution 125 which instituted a Judiciary Policy for Dealing with Conflicts of Interest, institutionalizing consensual means in solving conflicts of in-terest within the scope of the role of the Judiciary. Based on such a public policy, this paper analyzes the pre-procedural mediation in issues involving family rights as an instrument to promote access to justice. In order to achieve this aim, the case study approach was used, which focused on the pre-procedural mediations of family conflicts requested in CEJUSC/PG in 2019. Firstly, bibliographical and documentary research was carried out, seeking the contribution of several authors who state agreement on such a topic. Data collection was performed analysing the process of 169 requests for pre-procedural mediations, through an interview technique in which 13 applicants par-ticipated. The result of the analysis of quantitative data is reported by graphs and ta-bles. The interviews are analyzed using the methodology of collective subject dis-course. This study was able to show how the pre-procedural mediation of family con-flicts, along with the role played by of CEJUSC/PG, is an important instrument to pro-vide access to justice in the District of Ponta Grossa.
Keywords: Acesso à justiça; Mediação pré-processual; Conflitos familiares; CEJUSC/PG; Access to justice; Pre-procedural mediation; Family conflicts; CEJUSC/PG; CNPQ::CIENCIAS SOCIAIS APLICADAS